Evaluation of sunflower genotypes for phosphorus acquisition and phosphorus partitioning: EVALUATION OF SUNFLOWER GENOTYPES FOR P ACQUISITION - A QURESHI AZIZ; M Y DUDHE; G SURESH (Journal of Oilseeds Research, 2013)
Field trials were conducted during winterseason of 2010 and 2011 to evaluate a total of 111 (52+59) sunflower genotypesfor phosphorus(P) acquisition in Vertisols having low status of available phosphorus(9.8 kg/ha). During the study the best genotypes were selected based on the following parameters: shoot drymatter yield, seed yield/plant, shoot P content, seed P content and total P removal. In the first year 22 best performing genotypes out of 52 were selected while, 20 genotypes were selected out of 59 in second year (2011-12). Genotype CMS-42-B had recorded highest P removal (1.71g/plant) followed by KBSH-44 (1.62 g/plant) > 150-R (1.41 g/plant) >ARM-239-B (1.33 g/plant) > GMU-389 (1.31 g/plant) > KBSH-1 (1.30 g/plant) in first year. The phosphorus acquisition in sunflower genotypes depended on theirshoot drymatter,seed yield and their P contents. During 2011-12, the highest P removal was recorded in GMU-38 (2.2 g/plant) followed by GMU-128, KBSH-1, KBSH-44, GMU-3, GMU-5, DRSH-1, GMU-116 and CMS-42-B in descending order. It was noticed that genotype CMS-42-B wasfound best in acquiring P in both the years of study with 51% of its uptake was partitioned into seeds in 2010-11 and 52.3% in 2011-12. Though, CMS-42-B had removed lower amounts of total phosphorus (1.68 g/plant), it showed high internal distribution of acquired phosphorus towards seed (52.3%) in comparison to genotypes GMU-38, GMU-5 and KBSH-1.